2022
DOI: 10.3389/fcimb.2022.991150
|View full text |Cite
|
Sign up to set email alerts
|

2’-Fucosyllactose inhibits proliferation of Clostridioides difficile ATCC 43599 in the CDi-screen, an in vitro model simulating Clostridioides difficile infection

Abstract: BackgroundClostridioides difficile is a Gram-positive anaerobic bacterium that can produce the toxins TcdA and/or TcdB and is considered an opportunistic pathogen. C. difficile is mainly transmitted as endospores, which germinate to produce the pathogenic vegetative cells under suitable conditions in the gut. To efficiently screen novel therapeutic- interventions against the proliferation of C. difficile within a complex microbial community, platforms are needed that facilitate parallel experimentation. In ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…As a result of these changes in microbial composition, metabolic profiles of in vitro-cultured microbiota also changed, positively influencing the sporulation process of C. difficile [ 34 ]. The effect of specific dietary compounds on C. difficile proliferation was also evaluated in an in vitro model mimicking CDI, named CDi-Screen [ 35 ]. Vegetative cells and spores of C. difficile ATCC 43599 were separately co-cultured with the gut microbiota in the model in the presence of 2′-fucosyllactose (2′-FL), which was shown to significantly inhibit the overgrowth of C. difficile in vitro, reduce its abundance, and enhance the levels of Blautia in a dose-dependent manner [ 35 ].…”
Section: Intestinal Pathogens and Gut Microbiotamentioning
confidence: 99%
“…As a result of these changes in microbial composition, metabolic profiles of in vitro-cultured microbiota also changed, positively influencing the sporulation process of C. difficile [ 34 ]. The effect of specific dietary compounds on C. difficile proliferation was also evaluated in an in vitro model mimicking CDI, named CDi-Screen [ 35 ]. Vegetative cells and spores of C. difficile ATCC 43599 were separately co-cultured with the gut microbiota in the model in the presence of 2′-fucosyllactose (2′-FL), which was shown to significantly inhibit the overgrowth of C. difficile in vitro, reduce its abundance, and enhance the levels of Blautia in a dose-dependent manner [ 35 ].…”
Section: Intestinal Pathogens and Gut Microbiotamentioning
confidence: 99%
“…Participants gave written informed consent. Fecal samples were collected and prepared as described [ 30 , 31 ] with some modifications. In brief, fecal samples were collected by the volunteers with the FecesCatcher (fecesvanger.nl).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to serving as prebiotics for bacteria in the infant gut, other functions of HMOs include modulating epithelial and immune cell responses and acting as decoy receptors to reduce the attachment of pathogenic microbes to cell surface receptors (12). As such, HMOs have been shown to prevent pathogen adhesion to host epithelia for multiple enteric bacteria such as Campylobacter jejuni, Clostridioides difficile and Escherichia coli O157 as well as viruses such as rotavirus, coxsackievirus class A type 9 and SARS-CoV-2 (13)(14)(15)(16)(17)(18). Previous X-ray crystallography studies with three HuNoV genotypes (GI.1, GII.10 and GII.17) have shown that 2-fucosyllactose (2'FL), an α-1,2-fucosylated HMO, binds to the protruding domain of the HuNoV capsid protein VP1 in a similar pocket as HBGAs (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%